Risk of Falls, Fear of Falling, and Loss of Autonomy on Old - Pereira, Catarina (2011)
This thesis examined the importance of physical activity and fitness, in the performance of daily living activities (ADLs). The research comprised 600 adults over 50 year old and 79 young adults, of whom 106 old adults were followed-up for a 5 years period. Falls and injuries, fear of falling, disability in performing ADLs, usual physical activity, intrinsic (physical fitness, body composition and health status) and extrinsic risk factors (environmental hazards) for these events/behaviors were evaluated. Data were analyzed by using comparisons, correlations and regression analyses. Results showed that frailty regarding intrinsic factors leads to an increase in the risk of extrinsic factors and limit the performance of ADLs. The number of co-morbidities was the main intrinsic risk factor for falls and ADL disability. Fear of falling was found to be a higher risk for ADL disability than falls and injuries. Decreased balance was the physical fitness parameter that contributed most for falls, while reduced aerobic endurance was the most important parameter for ADL disability.